CCAFS Gender Strategy - Ashby, Jacqueline A.; Kristjanson, Patricia M.; Thornton, Philip K.; Campbell, Bruce M.; Vermeulen, Sonja J.; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
This Gender Strategy is intended to strengthen CCAFS’ development impact through the integration of gender issues into research in keeping with commitments in the CGIAR Strategy and Results Framework to ensure that rural women benefit from its contribution to poverty reduction, enhanced environmental resilience, improved food security, human health and nutrition. CCAFS plans to situate its gender strategy within a broader strategy addressing social inclusion for different social groups while bearing in mind that women are central to agriculture in developing countries. This Strategy was prepared following CGIAR Guidelines for CRP Gender Strategy1 that focus on showing how the CRP will address issues of gender in its research (as distinct from gender in the workplace which will be handled separately). Accordingly, the document is organized into seven sections that together provide an explanation of how the CRP will address gender issues relevant to its research outputs, activities and outcomes and against which the CRP will report in future, as part of the CGIAR annual monitoring process.